Impact of culture on the pursuit of beauty: Evidence from five countries - MADAN, Shilpa (Institutional Knowledge at Singapore Management University, 2018)
Human beings have always coveted beautiful objects, but the desire to look good is reaching new heights worldwide. Although the pursuit of beauty appears universal, industry evidence suggests that it is particularly strong in Asia. This research examines the effect of culture on the pursuit of beauty. Three studies provide converging evidence that interdependent self-construal increases the likelihood of using appearance-enhancing products. Study 1 operationalizes culture through nationality and self-construal and shows that Easterners (more interdependent) are more likely to use appearance-enhancing products than Westerners (less interdependent). This use is driven by interdependents’ tendency to conform to societal norms, which in turn leads to heightened self-discrepancy (Study 2). The use of appearance-enhancing tools helps minimize this discrepancy. Study 3 shows that strength of norms moderates the impact of interdependence on the use of appearance-enhancing tools. When norms are loosely defined and adherence is not strictly enforced, interdependents’ appearance enhancement tendency is reduced. This research offers actionable insights into the pursuit of beauty, marketing of beauty brands, policy making, and consumer well-being.